On the Nearest Real Singularities of a Single Loop Feynman Diagram - M. Barmawi (Journal of Mathematical and Fundamental Sciences, 1963)
Ichtisar. Disini dibahas sarat-sarat untuk singularitas riel terdekat dari amplitude proses2 jang ditundjukkan oleh suatu diagram Feynman dengan satu lingkaran tertutup jang umumnja menjatakan produksi dari partikel2. Telah ditundjukkan bahwa sarat Landau dan positipnja parameter Feynman jang bersangkutan tidak tjukup. Sarat selandjutnja jang masih harus dipenuhi ternjata merupakan perluasan dari sarat Karplus, Sommerfield dan Wichmann jang diketemukan untuk "fungsi tiga titik". Selandjutnya akibat sarat tambahan ini dibahas, dimana ditundjukkan pula hubungannja dengan "dugaan" (conjecture) dari Nambu dan Blankenbeckler jang ternjata umumnja tak benar. Pembahasan ini djuga dapat dipergunakan pada diagram Feynman jang sembarang. Abstract. The nearest singularities of production amplitude corresponding to a single loop Feynman diagram is discussed. It is shown that Landau condition and the positiveness of the Feynman parameter is not sufficient for the part of Landau curve to be the nearest real singularity. The additional condition is the generalized Karplus, Sommerfield and Wichmann condition, originally found in the 3-point function. The consequences of this additional condition is discussed and related to Blanken-beckler-Nambu conjecture. The discussion is also applicable to an arbitrary Feynman diagram.